IDENTIFICATION OF SCHOOL BULLYING BEHAVIOR IN HIGH GRADE STUDENTS OF STATE ELEMENTARY SCHOOL 001 BALAM JAYA KAMPAR - Rezinanda Saprila (Education Generation Journal, 2022)
This study aims to further identify bullying behavior in schools in the 001 Elementary High School Balam Jaya Kampar. This study uses a quantitative descriptive method. For the aspect of direct physical contact has the highest percentage of 90.26% with the "Very High" category, the verbal contact aspect has a percentage of 83.71% with the "Very High" category, the direct non-verbal behavior aspect has a percentage of 88.00% in the "Very High" category, while indirect non-verbal behavior has a percentage of 85.00% in the "Very High" category, it can be said from the four aspects of Bullying Behavior in Elementary High School Students Bullying School Behavior in Kampar Negeri 001 Balam Jaya the highest was direct verbal contact, and the lowest was indirect non-verbal behavior. So all those related to students such as principals, teachers, counseling guidance teachers, and parents respond to bullying behavior in small or large forms so as not to cause victims and have a detrimental impact on students.